ANALISIS KESALAHAN PESERTA DIDIK DALAM MEMECAHKAN SOAL LITERASI DAN NUMERASI : PENDEKATAN MELALUI PROSEDUR NEWMAN: ANALISIS KESALAHAN PESERTA DIDIK DALAM MEMECAHKAN SOAL LITERASI DAN NUMERASI: PENDEKATAN MELALUI PROSEDUR NEWMAN - Logistica, Raden Siti Aaisyah; Awalludin, Subhan Ajiz (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
Mathematical literacy and mathematical numeracy are basic skills that are crucial for educational progress and individual development. However, students' mathematical literacy and numeracy skills in Indonesia must still meet the expected standards. Therefore, this research aims to analyze students' errors in solving mathematical literacy and mathematical numeracy questions. This research uses qualitative research with a descriptive approach. In this study, six subjects were selected using a purposive sampling technique, with two subjects representing high, medium, and low ability categories. Subject selection criteria are based on the results of essay tests in the algebra domain. Mathematical literacy and mathematical numeracy abilities were analyzed through student error analysis using the Newman error indicator, which includes five procedures: (1) reading, (2) comprehension, (3) transformation, (4) process skills, and (5) encoding. The results showed that students' error rates varied depending on the level of mathematical literacy and numeracy skills. Subjects in the high ability category generally need to improve comprehension, processing skills, and answer writing stages. Subjects in the medium ability category typically make mistakes in the reading, comprehension, processing skills, and answer writing stages. Then, subjects in the low category tend to make mistakes at all stages of analysis. The recommendations from this study are expected to provide valuable insights for educators in designing more effective learning strategies to overcome these errors.